Evaluasi Penerapan Metode Uji ASTM D-86 untuk Penentuan Sifat Volatility Solar B30 - Arluky Novandy (Jurnal Nasional Pengelolaan Energi MigasZoom, 2021)
Abstract The distillation test is one of the important test parameters in determining the quality of fuel, especially in determining the volatility characteristic. In the domestic market for diesel fuel types, the distillation method used is ASTM D86-17. This study discusses the analysis of the application of the ASTM D86-17 distillation method on Biosolar B30. The F test shows that the ASTM D86-17 method can be used for the distillation of Biosolar B30, while the t test shows that the mean (mean) of refinery diesel and biodiesel B30 distillation data are not the same so there is a significant difference.